HUBUNGAN PEMAHAMAN BHINNEKA TUNGGAL IKA DENGAN KESADARAN BERKEBHINEKAAN GLOBAL - Sabrina, Anggela; Narmoatmojo, Winarno; Triyanto (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to prove whether there is a relationship between understanding of Unity in Diversity and global diversity awareness of students in class X SMKN 3 Sukoharjo, with a correlational quantitative method. The variables are the understanding of Bhinneka Tunggal Ika and global diversity awareness. The population is 500 students in class X SMKN 3 Sukoharjo with a sample of 70 students in class X Marketing A and X Automotive Engineering A. The sampling technique is cluster random sampling. Validity test with point biserial test and product moment test. Spearman Brown and Cronbach Alpha reliability tests. Normality test with liliefors test and linearity test with lack of fit test method. Hypothesis testing using pearson correlation product moment test and regression equation. The results of the study are Sig value. 0.000 and the value (r) 0.837, indicating that students who have a high understanding of Bhinneka Tunggal Ika have a high awareness of diversity. The results strengthen the Affective-Cognitive Consistency theory by Rosenberg.